Youth DIY-culture: a perspective of cultural sociological study - Kashpar, Vadim I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article discusses the essential characteristics of the phenomenon of youth DIY-culture in the modern context and suggests a theoretical and methodological perspective for studying it on the basis of the sociology of the late E. Durkheim and the project of «A strong program in cultural sociology» by J. Alexander and F. Smith. In the process of theoretical substantiation of this approach using the concept of cultural performance revealed fundamental contradictions between collective representations and social practices of DIY-culture representatives. According to a study of the social practices of DIY-culture, it was concluded that there are deep cultural foundations for the transformation of the identity of the studied social actors.